Evaluasi Kepuasan Pengguna Website Pemerintah sebagai Media Layanan Informasi Publik - Fiby Nur Afiana; Razel Syanahieskara; Gustin Setyaningsih (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
The government website serves as a medium for disseminating public information, providing transparency, and improving the quality of public services. However, in reality, some people still experience difficulties in accessing the government website, so an evaluation is needed to determine the level of user satisfaction with the services provided. This study aims to trigger user satisfaction with the Purbalingga Regency Government website using the End User Computing Satisfaction (EUCS) method. This method measures user satisfaction based on five main dimensions: content, accuracy, format, ease of use, and timeliness. The study was conducted through several stages: problem identification, data collection using questionnaires to the public as website users, and data analysis using the EUCS method. The results of the study indicate that partially there are two independent variables that influence user satisfaction, while the other three variables do not have a significant effect. However, simultaneously, all five variables have a significant influence on user satisfaction. The results of this study are expected to be used as evaluation material for local governments in improving the quality of website services to the public